O mito do vampiro na literatura e no cinema: a influência de Drácula, de Bram Stoker - Santanna, Diogo Ferraz (2015)
This work has as theme the permanence of the vampire myth in literature and cinema of centuries XX and XXI. Focusing on the importance that Dracula, by Bram Stoker, has to this permanence, the main objective is to check the specific points of this book's influence over the vampire representations after its publication. In order to achieve this goal, literary works about vampires which had been written before Dracula are analyzed and, after this, the novel Dracula itself, in order to understand the relation between the book with what had been already represented before it in terms of characteristics and themes of the vampire myth. Ultimately, Dracula's influence is analyzed by four film adaptations that can try an approach to the novel's plot or only use the characters presented in the novel. The methodology used in this work is essentially bibliographic, considering the term's scope for textual and audiovisual materials. The theoretical framework is based on myth and comparative literature studies, fiction characters and adaptation studies and texts which deal with the vampire myth, from its appearance to its insertion in literature. It is concluded that Dracula contributed to the permanence of vampire myth in artistic manifestations of centuries XX and XXI, regarding both the specific characteristics of this mythical being and the topics addressed in the adapted work and its adaptations.